Chimerism and phenotypic analysis of intraepithelial and lamina propria T cells isolated from human ileal biopsies after intestinal transplantation - Katherine D. Long; Jianing Fu (STAR Protocols, 2023)
Summary: Understanding immune cell dynamics after intestinal transplantation has provided new insights into human lymphocyte biology. However, isolating and characterizing such cells can be challenging. Here, we provide a protocol to isolate intraepithelial and lamina propria lymphocytes from human ileal biopsies. We describe techniques for flow cytometric analysis and determination of multilineage chimerism and T lymphocyte phenotypes. This protocol can be modified to isolate and analyze lymphocytes from other tissues.For complete details on the use and execution of this protocol, please refer to Fu et al. (2019)1 and Fu et al. (2021).2 : Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics.